DD Genotype of ACE Gene I/D Polymorphism Is Associated With Behcet Disease in a Turkish Population - Yigit, S.; Tural, S.; Rüstemoǧlu, A.; Inanir, A.; Gul, U.; Kalkan, G.; Akkanet, S. (Kluwer Academic Publishers rbk@louisiana.edu, 2013)
Behcet's disease (BD) is a chronic, multi-systemic and inflammatory disorder. The local renin-angiotensin system (RAS) in the vessel wall plays a role in the endothelial control and contributes to inflammatory processes. Angiotensin-converting enzyme (ACE) is the regulatory component of the RAS. This study was conducted in Turkish patients with BD to determine the frequency of I/D polymorphism genotypes of ACE gene. Genomic DNA obtained from 566 persons (266 patients with BD and 300 healthy controls). ACE gene I/D polymorphism genotypes were determined using polymerase chain reaction using I and D allele-specific primers. There was statistically significant difference between the groups with respect to genotype distribution (p<0.001). This study is the largest study in Turkish population that ACE gene I/D polymorphism investigated in BD. As a result of this study, ACE gene I/D polymorphism DD genotype could be a genetic marker in BD in Turkish study population. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Angiotensin-Converting Enzyme; Behcet's Disease; Polymorphism